2017
DOI: 10.18632/oncotarget.16239
|View full text |Cite
|
Sign up to set email alerts
|

Is preoperative chronic kidney disease status associated with oncologic outcomes in upper urinary tract urothelial carcinoma? A multicenter propensity score-matched analysis

Abstract: PurposeThe aim of this study was to determine the effect of preoperative chronic kidney disease (CKD) on the prognosis of patients with upper urinary tract urothelial carcinoma (UTUC) who had undergone radical nephroureterectomy (RNU).ResultsThe median follow-up period was 31.1 months (interquartile range: 16.2-55.7 months). Among the study patients, 224 patients in the non-CKD group were selected via propensity score matching. The median recurrence-free, cancer-specific, and overall survival were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Our results demonstrated that the prevalence of preoperative eGFR < 45 ml/min/1. As the prevalence of older age is higher among patients with urothelial carcinoma, studies report a recent increase in interest in the impact of preoperative renal insufficiency on poor prognosis [13][14][15]24,25]. Several studies have indicated an association between chronic kidney disease (CKD) and oncological outcomes associated with the effects of chronic inflammation, oxidative stress, metabolic disorder, uraemiaassociated immune deficiency, and frailty [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that the prevalence of preoperative eGFR < 45 ml/min/1. As the prevalence of older age is higher among patients with urothelial carcinoma, studies report a recent increase in interest in the impact of preoperative renal insufficiency on poor prognosis [13][14][15]24,25]. Several studies have indicated an association between chronic kidney disease (CKD) and oncological outcomes associated with the effects of chronic inflammation, oxidative stress, metabolic disorder, uraemiaassociated immune deficiency, and frailty [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also revealed that inflammatory markers such NLR and PLR were related to poor prognosis in univariate analysis, but not in multivariate analysis, although eGFR <60 ml/min/1.73 m 2 was found to be significantly associated with worse disease-specific and recurrence-free survival rates in patients with UTUC who underwent radical nephroureterectomy in multivariate analysis. In addition, others suggested CKD or end-stage renal disease may be involved in the progression or aggressiveness of UTUC, i.e., decreasing disease-specific and/or recurrence-free survival (27)(28)(29). Another study has suggested that UTUC patients with CKD undergoing hemodialysis lack the immune cells that recognize the tumor-associated antigens, thereby resulting in the acceptance of tumor progression under the status of immunological suppression (30).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with renal impairment are at risk of CVD [14], but the reason for the strong association between CKD and poor recurrence-free survival is not clear. Previous studies suggested kidney and urinary tract cancers are high risk for renal dysfunction due to the tumor location (obstruction, and/or reduction of nephron mass) [13,[15][16][17]. The prevalence of CKD in genitourinary cancers were reported 8.7-21.4% [15,18].…”
Section: Discussionmentioning
confidence: 99%